2020
DOI: 10.1101/2020.11.16.20232413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socioeconomic determinants of mobility responses during the first wave of COVID-19 in Italy: from provinces to neighbourhoods

Abstract: As the second wave of SARS-CoV-2 infections is surging across Europe, it is crucial to identify the drivers of mobility responses to mitigation efforts during different restriction regimes, for planning interventions that are both economically and socially sustainable while effective in controlling the outbreak. Here, using anonymous and privacy enhanced cell phone data from Italy, we investigate the determinants of spatial variations of reductions in mobility and co-location in response to the adoption and th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…This study also implies that socioeconomic, psychological, or other factors that characterize a change in human mobility may vary by different population groups and time frames, even in a small area [27][28][29]. Therefore, the movement-restriction policies will be more effective if the policies are clearly targeted to a specific population group at a specific time.…”
Section: Discussionmentioning
confidence: 99%
“…This study also implies that socioeconomic, psychological, or other factors that characterize a change in human mobility may vary by different population groups and time frames, even in a small area [27][28][29]. Therefore, the movement-restriction policies will be more effective if the policies are clearly targeted to a specific population group at a specific time.…”
Section: Discussionmentioning
confidence: 99%
“…By means of surveys delivered before the vaccination rollout in December 2020, authors found that vaccine information reduce adherence to social distancing, hygiene measures, and the willingness to stay at home. Several surveys conducted during the COVID-19 pandemic, well before any concrete hope for a vaccine, confirm this picture, provide hints of how the arrival of vaccines might corrode even more adoption, highlight how compliance is a complex multi-faced problem [5] and that risk-perception as well as NPIs adoption are indeed associated to several socio-economic determinants such as age, gender, wealth, urban-rural divide [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of socio-demographic and socio-economic characteristics in the adoption of NPIs has been also reported in other studies conducted by monitoring variations to aggregate mobility patterns before and during NPIs. Unanimously they indicate that disadvantaged groups, though less mobile before the pandemic, were not able to reduce their mobility (i.e., stay home) during the implementation of strict NPIs [30][31][32][33][34][35][36][37]. The literature aimed at estimating the epidemiological and societal impact of COVID-19 vaccines has been focused mainly on two very important points.…”
Section: Introductionmentioning
confidence: 99%
“…A potentially tractable formulation would be to use assume that aggregate infection is a CES function of jurisdiction-level policy. Second, the analysis does not consider the economic characteristics of different territories where the containment measures are to be implemented, including sectoral structure, labor linkages, and trade linkages (Acemoglu et al 2020;Barbieri et al 2020;Caselli et al 2020;Gauvin et al 2020;Burzynski et al 2020;Favero et al 2020). Future research may further investigate these aspects.…”
Section: Discussionmentioning
confidence: 99%